2014
DOI: 10.1037/a0037702
|View full text |Cite
|
Sign up to set email alerts
|

The power of presence: The role of mindfulness at work for daily levels and change trajectories of psychological detachment and sleep quality.

Abstract: In this research, we examined the role of mindfulness for recovery from work using a daily diary design (N ϭ 121; 5 days; 3 measurement occasions per day). The first goal of the study was to investigate the relationship of mindfulness with sleep quality and the mediating role of psychological detachment from a day-level perspective. A second goal was to extend the process perspective in recovery research beyond the day level and consider systematic change trajectories in recovery variables over the course of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
214
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(250 citation statements)
references
References 108 publications
13
214
3
5
Order By: Relevance
“…However, recent findings have shown that personal resources are important to become able to distance from work after a workday. For example, a high level of mindfulness may be necessary to keep mentally focused on the off-job activities once employees leave the workplace which in turn may promote psychological detachment from work (Hülsheger et al, 2014). Accordingly, one would expect that individuals low in mindfulness might find it more difficult to stop thinking about work, even when actively pursuing pleasurable leisure activities during non-work time, as they become less absorbed -which is consistent with the distraction hypothesis (Yeung, 1996).…”
Section: Discussionmentioning
confidence: 68%
“…However, recent findings have shown that personal resources are important to become able to distance from work after a workday. For example, a high level of mindfulness may be necessary to keep mentally focused on the off-job activities once employees leave the workplace which in turn may promote psychological detachment from work (Hülsheger et al, 2014). Accordingly, one would expect that individuals low in mindfulness might find it more difficult to stop thinking about work, even when actively pursuing pleasurable leisure activities during non-work time, as they become less absorbed -which is consistent with the distraction hypothesis (Yeung, 1996).…”
Section: Discussionmentioning
confidence: 68%
“…In respect to work-related rumination for example, workers may be provided with techniques or strategies to help them unwind post work (Cropley, 2015). Interventions in the form of CBT training or mindfulness (Hülsheger et al, 2014; Querstret et al, 2015, 2016) have been shown to reduce the frequency and intensity of work related thoughts. The present findings suggest that future interventions aiming to reduce work-related rumination should also address the issues relating to central executive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to confer benefits on various wellbeing 3 related outcomes; for example, coping capabilities, purposefulness in life and the experience of positive emotions (e.g., Fredrickson et al, 2008). With regard to occupational health, mindfulness has been shown to be effective in: reducing daily hassles, psychological distress, and medical symptoms (Williams, Kolar, Reger, & Pearson, 2001;Dane, 2011); reducing emotional exhaustion and improving job satisfaction (Hulsheger et al, 2013); increasing employee engagement (Leroy, Anseel, Dimitrova, & Sels, 2013); improving sleep quality (Wolever, Bobinet, McCabe, Mackenzie, Fekete, Kusnick, et al, 2012;Hulsheger, Lang, Depenbrock, Fehrmann, Zijlstra, & Alberts, 2014;Hulsheger, Feinholdt, & Nubold, 2015); reducing perceived stress (Wolever et al, 2012); and increasing psychological detachment from work and satisfaction with work-life balance (Michel, Bosch, & Rexroth, 2014).…”
Section: Mindfulnessmentioning
confidence: 99%